EFL Learners’ Perceptions of Using ELSA Speak for Speaking and Pronunciation Improvement - Najmah Syakiratun Niam; Muhammad Hifdil Islam; Feri Ferdiyanto (Journal of English Language and Education, 2026)
English speaking and pronunciation remain challenging for EFL learners, especially in non-English departments. Although mobile-assisted language learning has been widely studied, limited research explores students’ perceptions of AI-based pronunciation applications such as ELSA Speak. Therefore, this study investigates students’ perceptions of using ELSA Speak to improve speaking and pronunciation skills. This qualitative descriptive study involved 20 students from the English Club at Hafsawaty University, with five students selected for interviews. Data were collected through interviews, observation, and documentation. The findings show that ELSA Speak provides real-time feedback, increases students’ confidence, and supports independent learning. However, students also faced challenges, including internet dependency and limited free features. Overall, ELSA Speak is considered an effective tool for improving speaking and pronunciation skills among EFL learners.